Desmoplakin Is Required Early in Development for Assembly of Desmosomes and Cytoskeletal Linkage - Gallicano, G. Ian (The Rockefeller University Press, 1998)
Desmosomes first assemble in the E3.5 mouse trophectoderm, concomitant with establishment of epithelial polarity and appearance of a blastocoel cavity. Throughout development, they increase in size and number and are especially abundant in epidermis and heart muscle. Desmosomes mediate cell–cell adhesion through desmosomal cadherins, which differ from classical cadherins in their attachments to intermediate filaments (IFs), rather than actin filaments. Of the proteins implicated in making this IF connection, only desmoplakin (DP) is both exclusive to and ubiquitous among desmosomes. To explore its function and importance to tissue integrity, we ablated the desmoplakin gene. Homozygous −/− mutant embryos proceeded through implantation, but did not survive beyond E6.5. Mutant embryos proceeded through implantation, but did not survive beyond E6.5. Surprisingly, analysis of these embryos revealed a critical role for desmoplakin not only in anchoring IFs to desmosomes, but also in desmosome assembly and/or stabilization. This finding not only unveiled a new function for desmoplakin, but also provided the first opportunity to explore desmosome function during embryogenesis. While a blastocoel cavity formed and epithelial cell polarity was at least partially established in the DP (−/−) embryos, the paucity of desmosomal cell–cell junctions severely affected the modeling of tissue architecture and shaping of the early embryo.